Sombra modifica as respostas comportamentais e fisiológicas de vacas leiteiras de baixa a média produção em pastagens de sistemas de integração lavoura pecuária floresta - Reis, Natani Silva (2022)
Milk production in Brazil is concentrated mainly in the tropical region, with climatic characteristics of high temperatures, high air humidity and strong winds, which are factors that affect the comfort and well-being of lactating cows in pasture systems. Under these conditions, the presence of shade is essential to mitigate the effects of excess heat received through direct solar radiation, especially during the hottest hours of the day. The Crop-Livestock Forest Integration (ICLF) systems benefit both the animals in welfare conditions, the development of forage grasses, mitigation of greenhouse gas emissions, and the production of wood and non wood products for the producer's economic benefit. Lactating cows exposed to heat stress in pasture environments change their behavior in an attempt to maintain the homeostatic balance of exchanging internal heat with the environment. Rumination, idleness and activity times, as well as milk production, are affected by the environment the animal is exposed to. Physiological characteristics, such as rectal temperature, panting score, among others, may be impaired in more challenging environments for the animals. The morphological characteristics of coat color, skin, and hair thickness can help reduce the incident thermal load in conditions of direct solar radiation and high temperatures for dairy cows in pasture production systems. The objective of this study was to evaluate the behavioral and physiological responses of Gir and Girolando cows in integrated crop-livestock-forest (CLI) systems and in full sun.